Cell Culture Technology (Learning Materials in Biosciences,, 2018)
This textbook provides an overview on current cell culture techniques, conditions, and applications specifically focusing on human cell culture. This book is based on lectures, seminars and practical courses in stem cells, tissue engineering, regenerative medicine and 3D cell culture held at the University of Natural Resources and Life Sciences Vienna BOKU and the Gottfried Wilhelm Leibniz University Hannover, complemented by contributions from international experts, and therefore delivers in a compact and clear way important theoretical, as well as practical knowledge to advanced graduate students on cell culture techniques and the current status of research. The book is written for Master students and PhD candidates in biotechnology, tissue engineering and biomedicine working with mammalian, and specifically human cells. It will be of interest to doctoral colleges, Master- and PhD programs teaching courses in this area of research.